2005
DOI: 10.1111/j.1547-5069.2005.00063.x
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Practice Environment to Nurses' Job Satisfaction Through Nurse‐Physician Communication

Abstract: Factors in the practice environment contributed both directly to nursing job satisfaction and also indirectly through RN-MD communication. Study findings showed that a practice environment favorable to nurses improved both nurses' perceptions of their communications with physicians and their job satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
128
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(134 citation statements)
references
References 36 publications
1
128
0
1
Order By: Relevance
“…(Pullon, 2008). In the United States, a study of general nurses established strong relations between collegial relationships, stress, and nurses' job satisfaction (Manojlovich, 2005). In Australian the nurse-doctor relationship in mental health has been linked to the effect nurses have in decisions about patient treatment (Elsom et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Pullon, 2008). In the United States, a study of general nurses established strong relations between collegial relationships, stress, and nurses' job satisfaction (Manojlovich, 2005). In Australian the nurse-doctor relationship in mental health has been linked to the effect nurses have in decisions about patient treatment (Elsom et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, professional relationships between doctors and nurses have often remained realized as problematic (Pullon, 2008). In the United States, a study of general nurses established strong relations between collegial relationships, stress, and nurses' job satisfaction (Manojlovich, 2005). In New Zealand, a survey of general nurses found that positive nurse-doctor relationships were linked with advanced levels of communal functioning, vitality, and mental health (Budge, Carryer, & Wood, 2003).…”
Section: Nurse-doctor Relationshipsmentioning
confidence: 99%
“…2 Effective nurse-physician collaboration has been shown to reduce morbidity and mortality rates, cost of care, and errors and to improve job satisfaction and retention of nursing staff. [3][4][5][6] According to McConaughey 17 Rarely do health care professionals train as teams, yet evidence shows that team training improves team performance and safety outcomes. 19 Our study showed a statistically significant improvement in the perception by nurses and physicians of collaboration and decision making at 2 weeks after high-fidelity simulation team training.…”
Section: Discussionmentioning
confidence: 99%
“…Effective collaboration between registered nurses and physicians has been shown to reduce morbidity and mortality rates, cost of care, and medical errors and to improve job satisfaction and retention of nursing staff. [3][4][5][6] The nursing workforce is expected to decrease by 20% by 2020, putting the profession in a critical shortage. 7 Collaboration between nurses and physicians improves professional job satisfaction and is considered a high priority for retention purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Moral distress not only affects individual behavior but also the workplace environment. [52][53][54][55][56][57][58] For example, distressed health care providers can experience decreased job satisfaction, [59][60][61] unsettling physical symptoms such as insomnia and headaches, and disruptive psychological symptoms such as loss of confidence and self-worth. 26 Moreover, nurses' moral distress has been associated with absenteeism, burnout, intentions to quit, and leaving the profession.…”
Section: 50mentioning
confidence: 99%